Report of the Steering Committee on Secondary, Higher and Technical Education for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, Government of India, 2001)
The Report of the Steering Committee on Secondary, Higher and Technical Education for the Tenth Five-Year Plan (2002–2007), prepared under the aegis of the Planning Commission, outlines a comprehensive policy framework for strengthening post-elementary education as a critical driver of human resource development, economic growth, and social equity. Building upon the momentum generated by earlier reforms and guided by the National Policy on Education 1986, the report evaluates progress made during the Ninth Plan while identifying persistent challenges such as low enrolment at the secondary level, regional and gender disparities, quality concerns in higher education, and inadequate infrastructure. It highlights the pivotal role of secondary education as a bridge between elementary and higher education, emphasizing the need to expand access in response to rising demand from Universalisation of Elementary Education, while simultaneously addressing teacher preparation, infrastructure gaps, and curriculum modernization. In higher and technical education, the report underscores the urgency of improving academic standards, governance, research capacity, vocationalization, and industry linkage to enhance global competitiveness and innovation. Special attention is given to disadvantaged sections—including SC/ST communities, minorities, women, and persons with disabilities—to ensure inclusive participation and equitable opportunity. The Committee proposes targeted strategies, enhanced financial allocations, and systemic reforms to modernize curricula, strengthen institutions, expand vocational streams, and integrate emerging fields such as information technology. Overall, the report envisions a coordinated and quality-oriented expansion of secondary, higher, and technical education to support India’s transition toward a knowledge-based economy in the new millennium.
Government of India Planning Commission December - 2001
Keywords: Secondary Education; Higher Education; Technical Education; Tenth Five-Year Plan; Vocational Education; Education For Disadvantaged Sections; Quality Improvement; Gender Disparities; Human Resource Development; Curriculum Modernization; Educational Financing; Institutional Governance